The relationship between infrastructure and foreign investment inflows to South Africa - Taole, Tšepo Ntšoane (Research of GSB, 2018)
Foreign direct investment (FDI) has emerged as a major source of external capital for developing countries in Asia, South and Central America and Sub-Saharan Africa. However, Sub-Saharan Africa's share of global FDI compares unfavourably with that garnered by other developing regions in the world. Until recently, South Africa has been the top recipient of FDI inflows among SSA countries as it has benefitted from the relatively stable macroeconomic and political environment. South Africa is, however, afflicted by significant deficits in the quality and quantity of economic and social infrastructure. Empirical studies on the significance of infrastructure development and FDI inflows at country level in SSA are limited, as are empirical studies on the determinants of FDI inflows to SSA countries. It is against this backdrop that this research sets out to examine the relationship between infrastructure and FDI inflows to South Africa between 1970 and 2015. Secondary time series data on indicators for infrastructure quality, infrastructure investment, market size, financial market development, macroeconomic stability, and trade openness was collected for empirical analysis. In accordance with time series analysis of macro-economic data, unit root and cointegration tests were performed prior to estimation of the error correction model. The results of the research indicate that infrastructure quality, financial market development, trade openness, and market size all had a positive impact on FDI inflows in the long run, although significantly so in the case of the latter two indicators. Infrastructure investment stability had a negative but insignificant impact, while inflation had a negative but statistically significant impact on FDI inflows. In the short run, only trade openness and financial market development had a positive but statistically insignificant impact on FDI inflows. The other indicators reflected a negative and insignificant impact on FDI inflows. The results of the research suggest that besides advancing macroeconomic stability, the South African government should also foster inclusive economic growth and development which can enhance the country's attractiveness for FDI over the long-term.